Reconciling the Ministerial Exception and Title VII: Clarifying the Employer’s Burden for the Ministerial Exception - Amy Dygert (Washington University Journal of Law & Policy, 2019)
This note considers the consequences of the Supreme Court’s decision in Hosanna-Tabor Evangelical Lutheran Church and Sch. v. Equal Emp’t Opportunity Comm’n. In Hosanna-Tabor a unanimous Court declared the Constitution prevents federal non-discrimination law from being applied to “ministers.” However, the Court did not define the term minister. This note summarizes lower court decisions attempting to define this term. Building on these decisions the author proposes a three-prong test for determining whether a church employee should be classified as a minister.
Keywords: Ministerial exception; Employer; Employee; Minister; Church; Title VII; Hosanna-Tabor Evangelical Lutheran Church and Sch. v. Equal Emp’t Opportunity Comm’n; EEOC